The box tree moth Cydalima perspectalis: a review of biology, invasiveness, management practices and future perspectives of control strategy in Europe - Marta Budziszewska; Paweł Krystian Bereś (Journal of Plant Protection Research)
The box tree moth, Cydalima perspectalis (Lepidoptera: Crambidae), is a significant invasive pest threatening boxwood (Buxus spp.) in Europe, North America, and parts of Asia. Since its initial detection in Europe in 2006, C. perspectalis has spread rapidly, causing widespread damage to both ornamental and wild boxwood populations. Although extensive investigations have been conducted on its biology, reproduction, ecology, and phenology, achieving fully sustainable control strategies in Europe remains challenging, even with numerous studies and pest management efforts documented in the literature. It is a highly polivoltine species, with larvae that aggressively consume boxwood foliage leading to defoliation and plant death. The economic impact in Europe has been particularly severe in natural landscapes, especially in historical gardens. C. perspectalis is highly adapted to feeding on boxwood. It is plausible that the microbiome of larvae might detoxify phytocompounds and modify plant defense thus facilitating their survival and proliferation. This review consolidates the current knowledge on C. perspectalis, including its biology, origin, and distribution. Based on currently available literature, effective management strategies, which primarily rely on monitoring and early detection, are discussed. Due to the challenges in controlling this pest and the lack of effective natural enemies an integrated pest management (IPM) approach is recommended. This strategy combines biological, chemical, and mechanical methods to reduce populations and limit their destructive impact. Furthermore, the pest’s ability to neutralize the natural toxins in boxwood leaves increases the risk of insecticide resistance development. Consequently, understanding the microbial interactions between C. perspectalis and its host plant could offer further pest control strategies by targeting the microbiome to disrupt the detoxification process, making the insect more susceptible to boxwood defenses.